2011
DOI: 10.1007/s10862-011-9267-0
|View full text |Cite
|
Sign up to set email alerts
|

Should Social Aggression be Considered “Antisocial”?

Abstract: There is converging evidence that physical aggression and non-aggressive rule-breaking constitute meaningfully distinct, if somewhat overlapping, dimensions of antisocial behavior, with different developmental trajectories, demographic correlates, and etiologies. Social aggression can also be factor-analytically and demographically distinguished from physically aggressive and rule-breaking antisocial behavior. However, there is ongoing debate as to whether social aggression should also be considered "antisocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 51 publications
(68 reference statements)
3
46
0
5
Order By: Relevance
“…These results also add to the large body of literature supporting a distinction between aggressive and rule-breaking dimensions of antisocial behavior in children. For example, aggression is more strongly associated with negative emotion and affective dysfunction (Burt & Donnellan, 2008, 2009; Burt, 2012; Moffitt, 1993, 2003; Tackett, 2010; Verona, Patrick, & Lang, 2002) while rule-breaking is more strongly associated with impulsivity (Burt & Donnellan, 2008, 2009; Burt, Donnellan, & Tackett, 2012; Hopwood et al, 2009; Moffitt, 2003; Tackett, 2010). In addition, aggression is uniquely associated with executive dysfunction (Barker et al, 2007; Barker, Oliver, Viding, Salekin, & Maughan, 2011; Hancock, Tapscott, & Hoaken, 2010; Miura, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These results also add to the large body of literature supporting a distinction between aggressive and rule-breaking dimensions of antisocial behavior in children. For example, aggression is more strongly associated with negative emotion and affective dysfunction (Burt & Donnellan, 2008, 2009; Burt, 2012; Moffitt, 1993, 2003; Tackett, 2010; Verona, Patrick, & Lang, 2002) while rule-breaking is more strongly associated with impulsivity (Burt & Donnellan, 2008, 2009; Burt, Donnellan, & Tackett, 2012; Hopwood et al, 2009; Moffitt, 2003; Tackett, 2010). In addition, aggression is uniquely associated with executive dysfunction (Barker et al, 2007; Barker, Oliver, Viding, Salekin, & Maughan, 2011; Hancock, Tapscott, & Hoaken, 2010; Miura, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, entitled women are more likely to endorse benevolent sexism, believing that they are different from men and should be treated in a special manner (Hammond, Sibley, & Overall, 2014). Furthermore, entitled individuals are more likely to break rules and make unethical decisions (Burt, Donnellan, & Tackett, 2012;Greenberger et al, 2008;Tamborski, Brown, & Chowning, 2012). They are also more likely to be unhappy with their current situation; for example, they report reduced job satisfaction (Harvey & Martinko, 2009), perceive that they are being treated poorly by others (Harvey, Harris, Gillis, & Martinko, 2014), and believe that their time is being wasted (O'Brien et al, 2011).…”
mentioning
confidence: 99%
“…Although anger and aggression are two separate constructs, the former may serve as a precursor to the latter. Burt, Donnellan, and Tackett (2012) reported that aggression was associated with higher levels of anger among undergraduates; however, caution should be taken to interpret such findings in probabilistic rather than deterministic terms.…”
Section: Resultsmentioning
confidence: 97%